2011
DOI: 10.1007/s10584-011-0059-z
|View full text |Cite
|
Sign up to set email alerts
|

Climatic conditions and their impact on viticulture in the Upper Moselle region

Abstract: Climate parameters, especially temperature, sunlight, and precipitation, play a decisive role in growing and maturing processes. The aim of this study is to investigate the relationship between climate variability and variations in phenological events in viticulture. Long time series of daily meteorological observations are used to quantify these relations. The primary aim is to predict the date of phenological events by relationships between plant morphology and environmental conditions. Causal relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 16 publications
3
45
1
Order By: Relevance
“…Earlier maturity of wine grapes has been associated with increasing temperature and decreasing soil water content during the growing season in Australia (Webb et al 2012), but this conclusion was apparently inconsistent with long-term trends of annual rainfall (White 2013). According to Urhausen et al (2011), who analyzed the relationship between various climatic parameters and phenological stages in viticulture, only temperature-based predictors showed sufficient skill. In contrast, Ramos et al (2015) found high correlations between the veraison date and temperature variables as well as with precipitation−evapotranspiration data that were recorded during the bloom−veraison period.…”
Section: Relationship Between Grape Harvest Dates and Meteorological mentioning
confidence: 99%
“…Earlier maturity of wine grapes has been associated with increasing temperature and decreasing soil water content during the growing season in Australia (Webb et al 2012), but this conclusion was apparently inconsistent with long-term trends of annual rainfall (White 2013). According to Urhausen et al (2011), who analyzed the relationship between various climatic parameters and phenological stages in viticulture, only temperature-based predictors showed sufficient skill. In contrast, Ramos et al (2015) found high correlations between the veraison date and temperature variables as well as with precipitation−evapotranspiration data that were recorded during the bloom−veraison period.…”
Section: Relationship Between Grape Harvest Dates and Meteorological mentioning
confidence: 99%
“…The grapevine is particularly sensitive to its environment and has well-defined climatic conditions that enable it to grow and ripen its fruit to an optimum level (Urhausen et al 2011). Growing wine grapes outside of their optimum climatic thresholds can detrimentally impact the resulting wine quality.…”
Section: Introductionmentioning
confidence: 99%
“…The agricultural cultivation started in Roman times and continued with the constructions of monasteries in the Middle Ages along Central Europe (Urhausen et al, 2011). This dynamic was significantly increased by the intensification of production and harmful tilling of the soil, which led to a reduction in fertility (Boardman et al, 2003;Raclot et al, 2009).…”
Section: Introductionmentioning
confidence: 99%